High Gama-Aminobutyric Acid Contents Involved in Abamectin Resistance and Predation, an Interesting Phenomenon in Spider Mites - Xu, Zhifeng; Liu, Yanchao; Wei, Peng; Feng, Kaiyang; Niu, Jinzhi; Shen, Guangmao; Lu, Wencai; Xiao, Wei; Wang, Jinjun; Smagghe, Guy J.; Xu, Qiang; He, Lin (Frontiers in Physiology, 2017)
Abamectin has been widely used as an insecticide/acaricide for more than 30 years because of its superior bioactivity. Recently, an interesting phenomenon was identified in the carmine spider mite, Tetranychus cinnabarinus, an important pest in agriculture. The gamma aminobutyric acid (GABA) contents in a laboratory abamectin resistant strain of T. cinnabarinus (AbR) were significantly increased. Decreases in activity and mRNA expression of GABA transaminase (GABA-T) were responsible for GABA accumulation in AbR mites. To clarify the mechanism of GABA accumulation mediated abamectin resistance, three artificial approaches were conducted to increase GABA contents in susceptible mites, including feeding of vigabatrin (a specific inhibitor of GABA-T), feeding of exogenous GABA, and inhibition of GABA-T gene expression. The results showed that susceptible mites developed resistance to abamectin when the GABA contents were artificially increased. We also observed that the mites with higher GABA contents moved more slowly, which is consistent with the fact that GABA is an inhibitory neurotransmitter in arthropods. Subsequently, functional response assays revealed that predation rates of predatory mites on GABA accumulated abamectin-resistant mites were much higher than control groups. The tolerance to abamectin, slow crawling speed, and vulnerability to predators were all resulted from GABA accumulation. This relationship between GABA and predation was also confirmed in a field-collected population. Our finding indicates that predatory mites might be used as a tool for biological control to circumvent the development of abamectin resistance in mites.